The Integrated Maternity Management Model Through Promoting and Preventive Encouragement in the Attempts of Lowering the Maternal and Infant Mortality Rates - Diyan Indriyani; Asmuji Asmuji (Universitas Airlangga, 2014)
Introduction: Maternal Mortality Rate (MMR) and Infant Mortality Rate (IMR) remain the major indicator in assessing the level of certain country’s health quality. Both of Indonesia’s MMR and IMR levels are high enough compared to other ASEAN countries. To address this problem, a synergic cooperation among the cross-linked authorities is of prime important. One possible alternate option is building the Integrated Maternity Management model through promoting and preventive encouragement particularly designated for rural societies whose knowledge is relatively lower than the ones in urban areas.Methods: This research is conducted in Mumbulsari and Sukorambi Sub-Districts. The data collection techniques used in this research are survey/observation, interview, FGD, in-depth interview and, PRA conducted both to societies (local figures, people at risk, female teenagers, under-aged pregnant mother and young mothers) and local institutions and authorities.Result: This research has been able to formulate the Integrated Maternity Management model through promoting and preventive encouragement particularly designated for rural societies in the attempts of lowering the MMR and IIMR. This model has undergone trial, although the trial is simple in nature, by using the module medias of (1) teenager’s reproductive health which generated the average perception of the teenagers shown by the figure of 58,67 regarding their reproductive health prior to the intervention with minimum score of 30 and maximum score of 85. Meanwhile, upon applying the intervention, the average showed the figure of 81,33 with minimum score of 60 and maximum score of 95. The margin between the pre-test and post-test values reaches the figure of 22,36. This means that the supply of information regarding the module (1) which discusses the health reproductive issue generates better knowledge of those female teenagers concerning the respective issue.Discussion: Therefore, it is suggested that the implementation of the Integrated Maternity Management model through promoting and preventive encouragement put into action by initiating a comprehensive trial in order to generate the most suitable model, respectively.